Assessment of diagnostic performance of HE4 and CA125, individually and combined in epithelial ovarian cancer screening - Afrose, Taslima; Amin, Rogina; Chowdhury, Mina; Elora, Ashfi Laila; Jolly, Rabeya Sultana; Kader, Mousumi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Epithelial ovarian cancer (EOC) is one of the most lethal gynecological malignancies worldwide, often referred to as a "silent killer" due to its asymptomatic nature in the early stages. Proper diagnosis at early stage of Ovarian malignancy using biomarker is extremely important. The aim of this study was to evaluate the diagnostic accuracy of Human Epididymis Protein 4 (HE4) and Cancer Antigen 125 (CA125). Methods: This descriptive observational study was conducted in Dhaka Medical College Hospital from January 2021 to December 2021. Data were collected using a pre-designed data collection sheet encompassing demographics, clinical examination, and investigation results. After obtaining informed written consent, clinical examinations and ultrasound of the abdomen were conducted, followed by the collection of venous blood samples. Results: In our study predominant age group was 41-50 years (32.5%). Serum HE4 and CA125 concentrations were significantly higher in the ovarian cancer patients compared with those seen in patients with benign disease or in the healthy controls (p<0.05 in both). In patients with an adnexal mass, the area under the ROC curve was higher when the combination of the markers was used compared with use of CA125 only. Using ROMA, patients could be successfully classified into high- and low-risk group, with 57.7% sensitivity at a specificity of 63.9%. Conclusions: These findings suggest that measuring serum HE4 concentrations along with CA125 concentrations may provide higher accuracy for detecting early stage of Epithelial ovarian cancer.